The Interpreted Source Between Grammatical Application and Semantics (Journal of the College of Basic Education, 2025)
Modern linguists have played a significant role in focusing on the semantic aspects of the Arabic language, uncovering its intricacies, and explaining the impact of words and meanings on the human mind through various structures. Among these linguists are Dr. Mahdi Al-Makhzumi, Dr. Fadel Al-Samarrai, and Dr. Karim Nasih Al-Khalidi, who have emphasized the important distinction between verbal nouns (masdar) and nominalized clauses (al-masdar al-mu’awwal). They advocate for a deep understanding of the rich meanings conveyed when avoiding the excessive expansion of syntactic rules.This research examines the nominalized clause (masdar mu’awwal) and the perspectives of both ancient and modern scholars regarding its structure. It explores nominalizing particles, their grammatical cases, and how they integrate into sentences. Additionally, Quranic verses are analyzed to demonstrate the application of these structures in classical Arabic texts. The study highlights selected verses to clarify the differences in meaning when using different forms of nominalization, such as the use of the emphatic particle “ إنَّ ” and its subject and predicate. This analysis sheds light on the impact of contextual meaning and the variations in interpretation. Previous studies on this topic have largely focused on traditional grammatical analysis of the nominalized clause. Some have provided theoretical explanations, while others have examined its application in Quranic discourse. Among the notable studies are Dr. Islam Mohammed Abdel Salam’s research on the shift from explicit verbal nouns, published in Annals of Arts and Social Sciences, and Shatha Saleh’s master’s thesis, which analyzed nominalized clauses in the second half of the Quran, primarily focusing on their syntactic roles. This research deliberately avoids discussing subjunctive particles that require verb conjugation in the subjunctive mood, as the aim is not to explore syntax alone but rather to focus on the semantic significance in divine discourse. The study argues that these structures carry meanings that cannot be reduced to a single word, and their transformation into fixed syntactic rules may diminish their rhetorical power. The research concludes with findings, key references, and sources.